Peran Dana Desa Dalam Pembangunan Infrastruktur di Desa Bulusari - Naya Putri Syafira; Bintis Ti’anatud Diniati; Eliana Rahmadewi; Riska Fibrianti; Yunita Dian Anggraini (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study examines the governance of Village Funds in Bulusari Village and the influence of national policy changes on local development practices. The findings show that the village consistently follows government procedures despite shifting priorities between presidential administrations. Community participation remains central through hamlet and village meetings that gather local needs. Most proposals focus on infrastructure development and essential social services. A major problem identified is the lack of drainage affecting fish-farming households. Although drainage is repeatedly prioritized, its implementation remains limited due to national food-security policies. Transparency is maintained through documentation, information boards, and the use of the Siskeudes financial system. Regular supervision from district authorities strengthens accountability. However, limited administrative and digital skills among village officials hinder optimal reporting. Strengthening human resources and aligning local needs with national priorities are crucial for improving Village Fund management.